Lateral hypothalamic neurotensin neurons promote arousal and hyperthermia. - Fumito Naganuma; Daniel Kroeger; Sathyajit S Bandaru; Gianna Absi; Joseph C Madara; Ramalingam Vetrivelan (PLoS Biology, 2019)
Sleep and wakefulness are greatly influenced by various physiological and psychological factors, but the neuronal elements responsible for organizing sleep-wake behavior in response to these factors are largely unknown. In this study, we report that a subset of neurons in the lateral hypothalamic area (LH) expressing the neuropeptide neurotensin (Nts) is critical for orchestrating sleep-wake responses to acute psychological and physiological challenges or stressors. We show that selective activation of NtsLH neurons with chemogenetic or optogenetic methods elicits rapid transitions from non-rapid eye movement (NREM) sleep to wakefulness and produces sustained arousal, higher locomotor activity (LMA), and hyperthermia, which are commonly observed after acute stress exposure. On the other hand, selective chemogenetic inhibition of NtsLH neurons attenuates the arousal, LMA, and body temperature (Tb) responses to a psychological stress (a novel environment) and augments the responses to a physiological stress (fasting).